(untitled) (Revista de Estudos da Linguagem, 2024)
In this paper we analyze the semantic-syntactic behavior of a group of bare singular count nominals in Rioplatense Spanish. In particular, we study bare nominals that appear in argument position, as complements of the directional preposition a (to) (Ana va a consultorio/ ‘Ana goes to the clinic’), of the locative preposition en (in) (Los jugadores están en cancha/ ‘The players are in the football field’) and of transitive verbs (Juan mira tele/ ‘Juan watches tv’). First, some diagnostics are provided in order to show that these bare nominals behave like typical weak definites, as has been originally described in Carlson and Sussman (2005). After describing their distribution, we explore their semantic and syntactic nature using a non-pseudoincorporationist proposal –inspired by de de Swart (2015)–. In a nutshell, our analysis argues that these bare nominals project a defective syntactic structure, without overt phonological realization of D and without NumP. Furthermore, we assume that the determiner preserves its uniqueness and familiarity and we postulate that, in combination with the noun, it denotes an abstract entity or kind, and not a particular object (AGUILAR- GUEVARA, 2014). Finally, this study aims to contribute to the hypothesis that weak definiteness is a crosslinguistic phenomenon, that comprises both overt NPs and DPs.